DISCUSSION ON THE IMPACT OF THE GREEN INNOVATION STRATEGY ON CORPORATE FINANCIAL PERFORMANCE IN THE AUTOMOTIVE SECTOR - K. Devi; Indoria, Devadutta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Introduction: In the modern world of globalization increasing presence of technical aspect have opened the path for improved social development chances. These have also proved detrimental to the ecology and long-term growth in the automotive sectors. The goal of this research is to identify the mediating factors of developing the strategy that helps the industries to sustain the environment as well as earn maximum benefits. Literature Review: This research highlights the convenient approaches of the green innovative strategy of automotive industrial sectors. The impact of greener strategy on the link between sustainable culture and environmental aspects is discussed with critical analysis in terms of quality production of life and business improvement. Methodology: Primary quantitative approach of data collection helps to analyze the responses to 13 questions by 85 participants. This methodology part ensures the research analyzes primary data for solving all topic-related objectives and questions with positive positivism philosophy through SPSS software. Findings: Findings section includes the results of three hypotheses based on the survey results. The demographical analysis along with descriptive analysis is discussed with the relational value of the variables. Discussion: This green technology innovates the finance along with environmental regulation system in automotive sectors. Nature-focused development enabled critical ideas to connect, promoting sustainability and social conscience with industrial sectors. Conclusion: The conclusion part states that this study ensures the approach of the development approach of green policies of technology in the areas of budget management and production development.